Paradigma Governance dalam Penerapan Manajemen Kebijakan Sektor Publik pada Pengelolaan Sungai - RAHARJA, SAM’UN JAJA (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
The aim of this research is to analyze the public sector policy management in the management of Citarum river by using governance paradigm. The research used qualititive approach by using triangular sources techniques consisting of: the state, civil society, and private sector. The result shows that the management of drainage basin becomes a public matter involving the three main governance actors. However, the involvement of these three actors entails three implications: (1) the addition of core competence principle to the distribution of authority among actors, apart from ultra vires and general competence principles; (2) the addition of accessibility and effectiveness criteria in the affair distribution among the actors, apart from externality, efficiency, and accountability criteria; and (3) the revision of Government Regulation Number 38 year 2007 particularly on the affair distribution that involves non-state elements (civil society and private sectors) according to governance paradigm. More over there has been a need to revise the regulations related to the management of drainage basin.